2000
DOI: 10.1128/aem.66.5.1917-1922.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Products from the Incomplete Metabolism of Pyrene by Polycyclic Aromatic Hydrocarbon-Degrading Bacteria

Abstract: Pyrene is a regulated pollutant at sites contaminated with polycyclic aromatic hydrocarbons (PAH). It is mineralized by some bacteria but is also transformed to nonmineral products by a variety of other PAHdegrading bacteria. We examined the formation of such products by four bacterial strains and identified and further characterized the most apparently significant of these metabolites. Pseudomonas stutzeri strain P16 and Bacillus cereus strain P21 transformed pyrene primarily to cis-4,5-dihydro-4,5-dihydroxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 50 publications
4
89
1
4
Order By: Relevance
“…In a parallel study, a decrease in bioavailability was demonstrated (31). The accumulation of metabolites resulting from oxidation of PAHs can reduce the viability of several PAH degraders in addition to inhibiting the degradation of PAH (11,20,21). Nevertheless, this probably was not the case in this study, because polar metabolites determined by gas chromatography-mass spectrometry of the derivatized polar fraction did not accumulate in the soil (31).…”
Section: Discussionmentioning
confidence: 48%
“…In a parallel study, a decrease in bioavailability was demonstrated (31). The accumulation of metabolites resulting from oxidation of PAHs can reduce the viability of several PAH degraders in addition to inhibiting the degradation of PAH (11,20,21). Nevertheless, this probably was not the case in this study, because polar metabolites determined by gas chromatography-mass spectrometry of the derivatized polar fraction did not accumulate in the soil (31).…”
Section: Discussionmentioning
confidence: 48%
“…Strain P16 is able to grow, via salicylate, using phenanthrene (three rings), fluorene (two rings), naphthalene, and methylnaphthalenes (two rings) as the only carbon and energy sources (348,349). It is also able to transform pyrene (four rings) to nonmineral products (177). Interestingly, the phenanthrene bacterial growth rate increased in the presence of Tergitol NP10, an anionic surfactant.…”
Section: Biodegradation and Useful Properties For Biotechnological Apmentioning
confidence: 97%
“…The shunting of substrate through a new pathway, in combination with poor growth and suppressed degradation, suggest mechanisms of antagonism involving either toxicity or enzymelevel inhibition, both with precedents in published work on aromatic catabolism (19,25,57,65). For example, in Mycobacterium species and other bacteria, it is known that dihydrodiols are converted to diols, which autooxidize into toxic o-quinones (25,35,58,66). Detoxification involves retroconversion to a diol by quinone reductase enzymes, which can have narrow substrate ranges (66).…”
Section: Discussionmentioning
confidence: 99%